Analisis Pengaruh JUB, Kurs, Bi Rate, Dan Defisit Anggaran Terhadap Inflasi di Indonesia Tahun 2018-2022 - Gunawan Aji; Nuzul Al Rahmat Al Zaytun; Rizqianti, Dina; Ina Safarina Dewi; Sri Wulan Adiningsih (BADAN PENERBIT STIEPARI PRESS, 2023)
Inflation is an economic problem that has always been the main focus of governments around the world, including in Indonesia. The purpose of this study is to find out how Indonesia's inflation is affected by the JUB, the exchange rate, the BI rate, and the budget deficit. The research method is quantitative and data collection is in the form of secondary data obtained from the annual data of each variable. The results of the research conducted show that the JUB, exchange rate and BI rate have an influence on inflation. Meanwhile, the budget deficit has no effect on inflation.